Application of and Clinical Research on Enhanced Recovery After Surgery in Perioperative Care of Patients With Supratentorial Tumors - Wu, Jingmi; Zhang, Weina; Chen, Jie; Fei, Hui; Zhu, Hong; Xie, Haofen (Frontiers in Oncology, 2021)
Purpose: This study intends to explore the safety and effectiveness of the concept of enhanced recovery after surgery (ERAS) in the perioperative care of patients with supratentorial tumors. Methods: A total of 151 supratentorial tumor patients were enrolled in this study, and they were divided into control group (n=75) and observation group (n=76) according to the random number table method. Patients in the control group received routine neurosurgery care, and patients in the observation group received enhanced recovery after surgery care. The incidence of perioperative complications, postoperative hospital stays, early postoperative eating time, catheter removal time, and time to get out of bed were observed for the two groups of patients, and the quality of postoperative recovery was evaluated. Results: There was no statistically significant difference in the basic data of the two groups of patients, such as age, gender, lesion location and condition (P>0.05), and they were comparable. The observation group’s postoperative eating time, catheter removal time, and time to get out of bed were significantly earlier than those of the control group. Postoperative hospital stays and hospitalization expenses were less than those of the control group. There was a statistically significant difference in postoperative hospital stay between the two groups (P<0.05). Conclusion: Applying the ERAS concept to implement perioperative care for patients with supratentorial tumors is safe and effective. It can not only reduce after-surgical stress, accelerate postoperative recovery, but also shorten hospital stays and reduce hospital costs. It is worthy of clinical application.